Bridging Green Intellectual Capital and Green Organizational Culture toward Green Performance: A Green Innovation Perspective - Ernest Grace; Pungky Eka Ratnasari; Elly Romy; Acai Sudirman (Lembaga Publikasi Ilmiah Nusantara, 2026)
This study investigates the effects of green intellectual capital and green organizational culture on green performance, with green innovation as the mediator variable. Based on the natural resource-based view and knowledge-based theory, a quantitative explanatory methodology is used. Data were collected from the owners and managers of 250 environmentally oriented SMEs employing purposive sampling, which operate their businesses in an environmentally friendly manner. Valid and reliable measurement scales were applied, and the data were analyzed using structural equation modeling (SEM) to examine the direct and indirect effects. The findings reveal that green intellectual capital and green organizational culture positively and directly affect green innovation. In addition, a green organizational culture directly affects green performance. However, green intellectual capital has no direct effect on green performance. Instead, green intellectual capital affects green performance via green innovation. Moreover, green innovation mediates between green intellectual capital and green performance, and between green organizational culture and green performance. This study demonstrates that knowledge about environmentalism and organizational culture should be translated into innovative practice to achieve sustainable outcomes. The study implies that environmentally oriented SMEs should have strong green competence, a high level of environmental knowledge, and an organizational culture that supports innovation. From a practical perspective, it is recommended that owners/managers participate in environmental management training programs, implement green operations, and join the innovation cooperation network. Government policy could be directed to provide green training, green incentives, and technical support. This study expands the literature on the effects of green intellectual capital and green organizational culture on the green performance of environmentally oriented SMEs.